Evaluation of Parenting Patterns for Children and Teenagers in the Era of the Covid-19 Pandemic in Girian District, Bitung City - Rotty, Viktory N.J.; Rawis, Joulanda A.M.; Wullur, Mozes M.; Tinangon, Rinny M. (Budapest International Research and Critics University, 2021)
The teaching and learning process has changed as a result of the Covid-19 outbreak. Online learning is applied to limit human contact, especially children who belong to vulnerable groups. The reality is that learning online for only a hour each day becomes quite ineffective when considering the variety of courses offered. Informal schooling is critical during the Covid-19 outbreak. Education among the smallest community groups is critical for decreasing Covid-19 transmission. The goal of this research is to examine parenting styles among children and teenagers in the midst of the Covid-19 outbreak in Bitung City's Girian District. The method used in this research is a cross sectional study. The activity carried out in Girian District, Bitung City on the Socialization of Child and Teenagers Parenting in Girian Atas Village which is conducted in every month with different materials. The population in this study were 363 peoples. The data used was secondary data (report on the implementation of the Child and Teenagers Parenting Competition (PAAR)). The results showed that the Socialization of Parenting Patterns for Children and Teenagers in Girian Atas Village through various materials that had been implemented contributed to parenting patterns for children and teenagers. This is shown by the decline in juvenile delinquency cases before the Parenting of Children and Teenagers in 2019-2020 and cases of School Dropouts before the Parenting of Children and Teenagers in 2019-2020.